Sport and protest in the Black Atlantic
1 online resource (viii, 237 pages).
Keywords: "This is the first book to focus on race, sport, protest, and the Black Atlantic. It brings together innovative scholarship on African, African-American, Afro-European, Afro-Brazilian, and Afro-Caribbean sports in a manner that speaks effectively to the diversity of the African Diaspora, its history, and culture. The book explores the history of sports including baseball, basketball, boxing, football, rugby, cricket and track-and-field athletics to show athlete and fan protests in sport intersected with discourses of nationalism, self-fashioning, gender and masculinity, leisure and play, challenges of underdevelopment, and the idea of progress. It shows how sport in the African diaspora is a crucially important lens through which to understand the challenges, changes, and continuities of Black Atlantic history, the history of protest, and racism. This is fascinating reading for anybody with an interest in sport history, social and cultural history, post-imperial history and decolonisation, or the sociology of sport, race and political protest"--